Anger management: a case study among staffs at Lembaga Kemajuan Wilayah Kedah (KEDA) / Nabila Ahmad Nasir and Noor Aziatun Ayub - Ahmad Nasir, Nabila; Ayub, Noor Aziatun (2012)
The research was about the study on how to manage anger among staffs at Lembaga Kemajuan Wilayah Kedah (KEDA). The objectives of this research were to find out the useful ways of how employees managed their anger. The independent variables for this research were changing the environment, counseling, good communication and conflict resolution. The sampling frame of the research was drawn from KEDA and the sample size was I 00 respondents. The data was collected by using questionnaires that were personally distributed to 100 employees at there. The results revealed that most of the employees thought that having a good communication among each other will let them managed their anger efficiently. In contrast, attending counseling was the least chosen by them as one of the method to manage their anger.